A SSR kit to study genetic diversity in chickpea (Cicer arietinum L.). (16th July 2014) - Varshney, Rajeev; Thudi, Mahendar; Upadhyaya, Hari; Dwivedi, Sangam; Udupa, Sripada; Furman, Bonnie; Baum, Michael; Hoisington, David
Abstract : A chickpea simple sequence repeat (SSR) marker reference kit has been developed based on the genotyping of the global chickpea composite collection (3, 000 accessions) with 35 SSR markers. The kit consists of three pools of chickpea accessions along with supporting documentation on the SSR markers, polymerase chain reaction and detection conditions, and the expected allele sizes for each of the 35 SSR loci. These markers were selected based on quality criteria, genome coverage and locus-specific information content. Other important SSR selection criteria were quality of amplification products, locus complexity, polymorphism information content and well-dispersed location on a chickpea genetic map. The developed SSR kit has a wide range of applications, especially for genetic diversity studies in chickpea. Using the markers and reference accessions in the kit, scientists in other laboratories will be able to compare the genotypic data that they obtain for their germplasm with that obtained using the global composite collection.